2015
DOI: 10.3899/jrheum.150007
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of Global Assessments by Patient and Physician Is Higher in Female than in Male Patients Regardless of the Physician’s Sex: Data on Patients with Rheumatoid Arthritis, Axial Spondyloarthritis, and Psoriatic Arthritis from the DANBIO Registry

Abstract: In this study on Danish patients with RA, axSpA, and PsA, the PtGA was > 20 mm higher than the PGA in about half of the encounters, and more common in female patients of both female and male physicians. This finding highlights one of the challenges in shared decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 16 publications
5
45
3
1
Order By: Relevance
“…Higher global pain score was related to higher PGA, hence resulting in greater discordance between PGA and PhGA. This is similar to a Danish study on patients with spondyloarthropathy including axSpA in which pain was associated with higher discordance in PGA–PhGA …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Higher global pain score was related to higher PGA, hence resulting in greater discordance between PGA and PhGA. This is similar to a Danish study on patients with spondyloarthropathy including axSpA in which pain was associated with higher discordance in PGA–PhGA …”
Section: Discussionsupporting
confidence: 89%
“…Physician variables such as gender and age of the physician which may influence PhGA results were not included in the study. A Danish study showed that discordance was independent of physician's gender . Comorbidities such as chronic pain syndromes and mood disorders, which include fibromyalgia and depression, respectively, have been known to coexist with axSpA and may contribute to overestimation of patient‐reported symptoms such as pain scores, hence influencing discordance .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrepancies between physicians’ and patients’ assessments of their disease activity [13], treatment preferences [4,5], factors utilized in decision-making [68], and thresholds to change treatment plans [9], underscore the importance of including the patients’ perspective in outcomes research.…”
Section: Introductionmentioning
confidence: 99%